TiO2-supported Pt single atoms by surface organometallic chemistry for photocatalytic hydrogen evolution. Issue 44 (1st November 2019) - Jeantelot, Gabriel; Qureshi, Muhammad; Harb, Moussab; Ould-Chikh, Samy; Anjum, Dalaver H.; Abou-Hamad, Edy; Aguilar-Tapia, Antonio; Hazemann, Jean-Louis; Takanabe, Kazuhiro; Basset, Jean-Marie
Abstract : Platinum single atoms are grafted by SOMC on morphology-controlled TiO2 . Their structure is characterized by EXAFS and other techniques, and their activity and stability in HER and backwards reaction are studied and compared to Pt nanoparticles. Abstract : A platinum complex, (CH3 )2 Pt(COD), is grafted via surface organometallic chemistry (SOMC) on morphology-controlled anatase TiO2 to generate single, isolated Pt atoms on TiO2 nano-platelets. The resulting material is characterized by FT-IR, high resolution scanning transmission electron microscopy (HRSTEM), NMR, and XAS, and then used to perform photocatalytic water splitting. The photocatalyst with SOMC-grafted Pt shows superior performance in photocatalytic hydrogen evolution and strongly suppresses the backwards reaction of H2 and O2 forming H2 O under dark conditions, compared to the photocatalyst prepared by impregnation at the same Pt loading. However, single Pt atoms on this surface also rapidly coalesce into nanoparticles under photocatalytic conditions. It is also found that adsorption of CO gas at room temperature also triggers the aggregation of Pt single atoms into nanoparticles. A detailed mechanism is investigated for the mobility of Pt in the formation of its carbonyls using density functional theory (DFT) calculations.